2000
DOI: 10.1038/35050073
|View full text |Cite
|
Sign up to set email alerts
|

Subduction and collision processes in the Central Andes constrained by converted seismic phases

Abstract: The Central Andes are the Earth's highest mountain belt formed by ocean-continent collision. Most of this uplift is thought to have occurred in the past 20 Myr, owing mainly to thickening of the continental crust, dominated by tectonic shortening. Here we use P-to-S (compressional-to-shear) converted teleseismic waves observed on several temporary networks in the Central Andes to image the deep structure associated with these tectonic processes. We find that the Moho (the Mohorovicić discontinuity--generally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
331
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 345 publications
(382 citation statements)
references
References 27 publications
28
331
1
5
Order By: Relevance
“…Fluids have also been detected under the active volcanic front and below the Altiplano-Puna plateau and are thought to follow different pathways in the lithosphere . On the eastern border of the Altiplano, Wigger et al (1994) identified west-dipping structures in the crust, also confirmed by Yuan et al (2000) that are possibly related to the underthrusting of the Brazilian Shield beneath the Subandean and the Eastern Cordillera provinces. This situation has also been suggested by other authors (e.g.…”
Section: The Central Andes At 21°s and The Altiplano Plateaumentioning
confidence: 89%
See 3 more Smart Citations
“…Fluids have also been detected under the active volcanic front and below the Altiplano-Puna plateau and are thought to follow different pathways in the lithosphere . On the eastern border of the Altiplano, Wigger et al (1994) identified west-dipping structures in the crust, also confirmed by Yuan et al (2000) that are possibly related to the underthrusting of the Brazilian Shield beneath the Subandean and the Eastern Cordillera provinces. This situation has also been suggested by other authors (e.g.…”
Section: The Central Andes At 21°s and The Altiplano Plateaumentioning
confidence: 89%
“…Beneath the Altiplano-Puna region, a lowvelocity layer has been detected and explained as the possible presence of partial melting material (e.g. Chmielowski et al, 1999;Yuan et al, 2000;Brasse et al, 2002;Zandt et al, 2003). Fluids have also been detected under the active volcanic front and below the Altiplano-Puna plateau and are thought to follow different pathways in the lithosphere .…”
Section: The Central Andes At 21°s and The Altiplano Plateaumentioning
confidence: 95%
See 2 more Smart Citations
“…Th e current topographic slope on the eastern side is ca 2.2 -2.6 ° , and is maintained by an actively deforming wedge that is detached above the < 4 ° dipping ALVZ 39 ( Fig. 1c ) within the critical to subcritical fi eld ( Fig.…”
Section: Resultsmentioning
confidence: 99%